Zinc Biofortified Rice Varieties: Challenges, Possibilities, and Progress in India - Sanjeeva Rao, D.; Neeraja, C. N.; Madhu Babu, P.; Nirmala, B.; Suman, K.; Rao, L. V. Subba; Surekha, K.; Raghu, P.; Longvah, T.; Surendra, P.; Kumar, Rajesh; Babu, V. Ravindra; et al. (Frontiers in Nutrition, 2020)
Zinc malnutrition is a major issue in the developing countries where polished rice as a staple food. With the existing significant genetic variability for high zinc in polished rice, the development of biofortified rice varieties was targeted in India with support from HarvestPlus, Department of Biotechnology and Indian Council of Agricultural Research of Government of India. Indian Institute of Rice Research (IIRR) facilitates the rice varietal release through All India Coordinated Rice Improvement Project (AICRIP) and also supports rice biofortification program in India. Various germplasm sets of several national institutions were characterized at IIRR for their zinc content in brown rice using ED-XRF indicating the range of zinc to be 7.3 to 52.7 mg/kg. Evaluation of different mapping populations involving wild germplasm, landraces and varieties for their zinc content showed the feasibility of favorable recombination of high zinc content and yield. Ninety nine genotypes from germplasm and 344 lines from mapping populations showed zinc content of ≥ 28 mg/kg in polished rice meeting the target zinc content set by HarvestPlus. Through AICRIP biofortification trial constituted since 2013, 170 test entries were nominated by various national institutions till 2017 and four biofortified rice varieties were released. Only the test entry with target zinc content, yield and quality parameters are promoted to the next year, thus each test entry is evaluated for three years across 17 to 27 locations for their performance. Multi location studies of two mapping populations and AICRIP biofortification trials indicated the zinc content to be highly influenced by environment. The bioavailability of a released biofortified rice variety viz., DRR Dhan 45 was found to twice that of control IR64. The technology efficacy of the four released varieties developed through conventional breeding ranged from 48-75% with zinc intake of 38-47% and 46-57% of the RDA for male and female respectively. The observations from the characterization of germplasm and mapping populations for zinc content and development of national evaluation system for the release of biofortified rice varieties have been discussed in the context of the five criteria set by biofortification program.